Pengaruh Teknik Modeling Terhadap Kemandirian Memasang Kancing Siswa Disabilitas Intelektual Ringan Kelas IV Di SDLB YPAC Jember - Ali Bahroni; Khusna Yulinda Udhiyanasari; Arifah Nurhadiyati (Educatio, 2025)
This study aimed to explore the impact of the modeling technique on the independence of fourth-grade students with mild intellectual disabilities at SDLB YPAC Jember in the task of buttoning clothes. The research employed a Single Subject Research (SSR) method using an A-B design. The participant was a student identified as R. The study was conducted in two phases: a baseline phase consisting of five sessions without any intervention, and an intervention phase comprising ten sessions in which the modeling technique was applied. Data were collected through practical assessments of the student’s ability to button clothes and were analyzed descriptively by observing progress across the two phases.The findings revealed a notable improvement in the student’s skills. The average level of independence increased from approximately 63% during the baseline phase to around 82% following the intervention. Furthermore, the percentage of overlap between the phases was 0%, which provides strong evidence of the technique’s effectiveness. Based on these results, it can be concluded that the modeling technique significantly enhances students' independence in buttoning clothes. Therefore, it is recommended as a practical instructional method that special education teachers can adopt to support the development of daily living skills in students with special needs